PCR primed with minisatellite core sequences yields species-specific patterns and assessment of population variability in fishes of the genus Brycon - Wasko, A. P.; Galetti, P. M. (Wiley-Blackwell, 2003)
Minisatellite core sequences were used as single primers in polymerase chain reaction (PCR) to amplify genomic DNA in a way similar to the random amplified polymorphic DNA methodology. This technique, known as Directed Amplification of Minisatellite-region DNA, was applied in order to differentiate three neotropical fish species (Brycon orbignyanus, B. microlepis and B. lundii ) and to detect possible genetic variations among samples of the threatened species, B. lundii , collected in two regions with distinct environmental conditions in the area of influence of a hydroelectric dam. Most primers generated species-specific banding patterns and high levels of intraspecific polymorphism. The genetic variation observed between the two sampling regions of B. lundii was also high enough to suggest the presence of distinct stocks of this species along the same river basin. The results demonstrated that minisatellite core sequences are potentially useful as single primers in PCR to assist in species and population identification. The observed genetic stock differentiation in B. lundii associated with ecological and demographic data constitute a crucial task to develop efficient conservation strategies in order to preserve the genetic diversity of this endangered fish species.